The English Lecturers’ Strategies to Overcome the Difficulties of Islamic Education Students in TOEFL Reading Section - Chandra, Aqlisty Nia (AL-BURHAN, 2023)
This study aims to identify the strategies used by English lecturers in overcoming college students' difficulties in the reading section of TOEFL preparation. This research uses a qualitative approach with a descriptive research design. The data collected by interviews 2 English lecturers who are experienced in teaching TOEFL preparation in STAI Pati and 26 students of Islamic Education Program (PAI). The results of the study show that there are some factors affecting the difficulties of PAI students in doing TOEFL reading section: (1) students’ lack of vocabularies, (2) students’ less motivation, (3) study time limitation, and (4) time management. To overcome those difficulties, the English lecturers use several effective strategies include: creating fun learning, giving experience from successful test takers, giving relevant reading texts, and giving tips and trick doing TOEFL reading. The English lecturer also uses an approach based on students' needs and abilities, and provides constructive feedback to improve students' reading comprehension in TOEFL preparation.Keywords: Strategy, College Students’ Difficulties, Reading, TOEFL